Changes and determinants of unmet oral health treatment need - Torppa-Saarinen Eeva; Tolvanen Mimmi; Lahti Satu; Suominen Anna Liisa (WILEY, 2022)
Objectives
Our aim was to describe the nature and determinants of the changes in unmet treatment need between the years 2000 and 2011 after a major oral healthcare reform and a wider supply of subsidized care.
Methods
The study used a longitudinal sample (n = 3838) of adults who had participated in both the Health 2000 and 2011 surveys (BRIF 8901). Those reporting self-assessed treatment need without having visited a dentist in the previous 12 months were categorized as having unmet treatment need. Two logistic regression models were applied to determine the effects of predisposing and enabling factors on change in unmet treatment need. Model 1 was conducted among those who reported unmet treatment need in 2000 and evaluated the determinants for improvement. Model 2 was conducted among those who did not have unmet treatment need in 2000 to evaluate the risk factors for having unmet treatment need by 2011.
Results
Unmet treatment need was reported by 25% of the participants in 2000 and by 20% in 2011. Those with unmet treatment need in 2000 were less likely to report improvement by 2011 if they had poor subjective oral health, basic or intermediate education level, or poor perceived economic situation in 2000. Those who did not have unmet treatment need in 2000 were more likely to have it in 2011 if they were males or from northern Finland and less likely to if they came from central Finland or were older.
Conclusions
The wider supply of subsidized oral health care during the study years did not lead to complete elimination of treatment need. The determinants of unmet treatment need, such as low or intermediate education level and perceived economic difficulties, should be used in targeting the services at those with treatment need to achieve better oral health outcomes.